Crisis? What Crisis? Marginal Farming, Rural Communities and Climate Robustness: The Case of Northern Norway - Bjørkhaug, Hilde; Rønningen, Katrina (The International Journal of Sociology of Agriculture and Food, 2014)
Does it make sense to talk about a crisis in agriculture in one of the world’s wealthiest economies when significant quantities of public money are invested in the agricultural sector? Moreover, should one worry about the robustness of food production if it takes place at the margins of economic efficiency and where, consequently, importing food seems the simpler and cheaper option? Should agriculture in marginal areas have any role whatsoever in food production? Against the backdrop of national and international discourses on the need for increasing food production, this article analyses developments in Northern Norway in the aftermath of a year of major production crisis. The analysis uses large statistical data sets combined with qualitative information to draw a picture of agriculture in this region. We contend that marginal areas are important for maintaining agricultural production capacity but are unlikely to play a significant role in any potential increase in productivity unless new pathways are chosen for agricultural policies and production. However, the ability to maintain agricultural production systems and levels is being threatened by both economic and structural changes in agriculture and decreasing skills and knowledge of how to maintain and develop robust farming systems in these regions.